The killer angels [compact disc, unabridged] : a novel of the civil war - Shaara, Michael (Random House Audio, 2004)
In July of 1863, the Confederate Army, led by General Robert E. Lee, invaded the North, in order to deal a fatal blow to the Union Army. Lee's right hand man was the loyal General Longstreet. Opposing them was General George Meade, an unknown quantity at best. In the four most bloody and courageous days of the Civil War, their armies fought, one side for freedom and the other side for tradition. As the bodies piled up on the gory field, so did the dreams and hopes of the dead. Their futures were the ultimate casualties of war.